Implementasi Metode Queue Tree Dalam Management Bandwidth Game Online Berbasis Mikrotik - Nafsaka Diaz Prambudi, Arih; Rofiq, Muhammad (JURNAL SISTEM KOMPUTER ASIA, 2023)
Bandwidth Management is the process of controlling and measuring communications (network traffic and packets) on a network link, to avoid network congestion and poor performance on the network. Queue Tree is one of the bandwidth managemen in Mikrotik which is very flexible and quite complex. Queue requirements are more detailed based on service protocols, ports and others. Queue tree also uses the firewall mangle feature to determine which graphs we will limit. Mikrotik Routerboard is a device that functions as a gateway server that can share and provide security on the local network and also functions as a router, as a firewall, wifi device, bandwidth management, internet sharing, hotspot server, VPN Server and Client as a DNS server. With bandwidth management at Mr. Hendro's rented house, we will be able to control internet usage there so that the internet there becomes smooth. Besides that, managing bandwidth is not so difficult, as long as we understand and follow the rules of network creation